Muscle fibre typing, collagen composition analysis of breast and thigh meats in two breeds of chicken of different growth performance - Lee, Siang Pin; Abu Bakar @ Zakaria, Md Zuki (2010)
The present study was done to evaluate the type of muscle fibre composition in thigh and breast muscle of Red Jungle fowl and Ross. It was also to evaluate the collagen composition in thigh and breast muscle of Red Jungle fowl and Ross. The histological appearance and size of the muscle fibres of Red Jungle fowl and Ross were evaluated. Four wild adult Red Jungle fowl and four market adult Ross chicken were used in this study. Breast muscle (pectoral) and thigh muscle (gastrocnemius) were examined. Three stains were used in this study and there were Myosin ATPase stain, Masson Trichrome stain and Haematoxylin and Eosin stain. Myosin ATPase stain was used to evaluate the muscle fibres type composition, Masson Trichrome stain was used to evaluate the collagen content of the muscle and Haematoxylin and Eosin stain was used to evaluate the histological appearance and size of the muscle fibres. Histologically, the thigh muscle of the Red Jungle fowl has higher proportion of muscle fibres type I to type II than Ross. There were no difference in proportion of muscle fibres type I to type II of breast muscle in Red Jungle fowl and Ross. The thigh and breast muscle of Red Jungle fowl has high collagen content while Ross chicken’s thigh and breast muscle has less collagen content. The size of muscle fibre of Red Jungle fowl was small while that of Ross was big.